Together against sexual harassment rebranding of the UP Diliman Office of Anti-Sexual Harassment and an educational sexual harassment prevention campaign which aims to teach consent, boundaries, and different forms of sexual harassment to UP Diliman undergraduate students - Espinosa, Ma. Angela Luz L.; Sicat, Jose Manolo (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Sexual harassment is any sexual action that is unwelcomed or uninvited. It can happen anywhere and the UP Diliman campus is no exception to this. Over the years the cases of sexual harassment handled by the UP Diliman Office of Anti-Sexual Harassment has been increasing. The main perpetrators are male undergraduate students. In order to mitigate this the UP Diliman OASH has created a policy alongside with the Vice-Chancellor in order to require all departments of the UP Diliman community to attend an annual Anti-Sexual Harassment Seminar. Despite this policy, the awareness levels between UP Diliman undergraduate students about these topics still varies from person to person.

Thid research aims to find out the causes as to why sexual harassment is rampant with the UP Diliman undergraduate students and study appropriate visual communication tools in order to prevent future cases of this. Thie results showed that the perpetrators main reason as to why they committed such acts if because they are unaware that their actions were considered sexual harassment. It is also evident that most student have never received any formal training as to how to apply these topics on their day to day lives. With this, a rebrand of the Office of Anti-Sexual harassment is needed in order to encourage more students to report. This is also essential so that the visual identity of the OASH may be relatable and easier to connect towards the UP Diliman undergraduate students. Aside from that an educational campaign titled Know the Difference is necessary so that students may learn about consent, boundaries, and different forms of sexual harassment in an accessible and understandable way. This is so that they may also know how to apply these topics in real life situations.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 399-404
Keywords: Sexual harassment in education -- Philippines; Sexual ethics -- Instructional and educational works